A Study to Understand the Retirement Planning Behavior of Working Professionals in Mumbai City - Shaikh, Mr. Aftab; Katkar, Ms. Neena; Koli, Ms. Lipika; Bhakay, Dr. Jayashree (The journal of contemporary issues in business and government, 2022)
The explanatory research is designed to find out the retirement planning behavior of different working professionals of Mumbai City. The study attempts to understand the objective of the retirement planning of working professionals of different age cohort and their investment preferences to achieve their retirement objectives. The study also tries to found out the relationship between retirement planning and the different factors affecting retirement planning. 161 working professionals of different age groups have been taken for the study from Mumbai City. The study also aims to understand that does the investment avenues preference differ from different age cohorts?